Greek epic fragments : from the seventh to the fifth centuries BC - West, M. L. (Martin Litchfield), 1937-2015 (Cambridge (Mass.): Harvard university press, 2003)
"Greek epics of the archaic period include poems that narrate a particular heroic episode or series of episodes, and poems that recount the longterm history of families or peoples. They are an important source of mythological record. Here is a new text and translation of the examples of this poetry that have come down to us." "The heroic epic is represented by poems about Heracles and Theseus, and by two great epic cycles: the Theban Cycle, which tells of the failed assault on Thebes by the Seven and the subsequent successful assault by their sons; and the Trojan Cycle, which includes Cypria, Little Iliad, and The Sack of Ilion. Among the genealogical epics are poems in which Eumelus creates a prehistory for Corinth and Asius creates one for Samos. In presenting the extant fragments of these early epic poems, Martin West provides very helpful notes. His Introduction places the epics in historical context."--Jacket.
The Theban cycle. Oedipodea ; Thebaid ; Epigoni ; Alcmeonis -- The Trojan cycle. Cypria ; Aethiopis ; The little Iliad ; The sack of Ilion ; The returns ; Telegony, Thesprotis -- Poems on Heracles and Theseus. Creophylus, The capture of Oichalia ; Pisander, Heraclea ; Panyassis, Heraclea ; Theseis -- Genealogical and antiquarian epics. Eumelus (Titanomachia, Corinthiaca, Europia) ; Cinaethon ; Asius ; Hegesinous ; Chersias ; Danais ; Minyas ; Carmen Naupactium ; Phoronis -- Unplaced fragments (mostly ascribed to "Homer")
Index
Greek-English
Keywords: Epic poetry, Greek; Epic poetry, Greek -- Translations into English; Lost literature -- Greece